If a + b + c = 0, then the value of a^2/(a^2 – bc) + b^2/(b^2 – ca) + c^2/(c^2 – ab)
Solution Given: - The length of the kite's thread is 180 meters. - The angle between the thread and the horizontal line is \(60^\circ\). We can use trigonometry to find the height of the kite from the ground. The height (\(h\)) can be found using the sine function: \[ \sin \theta = \frac{\text{OpposRead more
Solution
Given:
– The length of the kite’s thread is 180 meters.
– The angle between the thread and the horizontal line is \(60^\circ\).
We can use trigonometry to find the height of the kite from the ground. The height (\(h\)) can be found using the sine function:
\[ \sin \theta = \frac{\text{Opposite side}}{\text{Hypotenuse}} \]
In this case, the opposite side is the height of the kite (\(h\)), and the hypotenuse is the length of the thread (180 meters):
\[ \sin 60^\circ = \frac{h}{180} \]
We know that \(\sin 60^\circ = \frac{\sqrt{3}}{2}\), so:
\[ \frac{\sqrt{3}}{2} = \frac{h}{180} \]
Solving for \(h\):
\[ h = 180 \times \frac{\sqrt{3}}{2} \]
\[ h = 90\sqrt{3} \]
The height of the kite from the ground is \(90\sqrt{3}\) meters.
See less
Solution Given: \[ a + b + c = 0 \] We need to find the value of: \[ \frac{a^2}{a^2 - bc} + \frac{b^2}{b^2 - ca} + \frac{c^2}{c^2 - ab} \] Since \(a + b + c = 0\), we can write \(a = -(b + c)\). Step 1: Substitute \(a = -(b + c)\) \[ \frac{(-b - c)^2}{(-b - c)^2 - bc} + \frac{b^2}{b^2 - c(-b - c)} +Read more
Solution
Given:
\[ a + b + c = 0 \]
We need to find the value of:
\[ \frac{a^2}{a^2 – bc} + \frac{b^2}{b^2 – ca} + \frac{c^2}{c^2 – ab} \]
Since \(a + b + c = 0\), we can write \(a = -(b + c)\).
Step 1: Substitute \(a = -(b + c)\)
\[ \frac{(-b – c)^2}{(-b – c)^2 – bc} + \frac{b^2}{b^2 – c(-b – c)} + \frac{c^2}{c^2 – b(-b – c)} \]
Step 2: Simplify
\[ \frac{(b + c)^2}{(b + c)^2 – bc} + \frac{b^2}{b^2 + bc – c^2} + \frac{c^2}{c^2 + bc – b^2} \]
Step 3: Simplify further
\[ \frac{(b + c)^2}{b^2 + c^2 + 2bc – bc} + \frac{b^2}{b^2 + c^2 + bc} + \frac{c^2}{b^2 + c^2 + bc} \]
\[ \frac{(b + c)^2}{b^2 + c^2 + bc} + \frac{b^2}{b^2 + c^2 + bc} + \frac{c^2}{b^2 + c^2 + bc} \]
Step 4: Combine the fractions
\[ \frac{(b + c)^2 + b^2 + c^2}{b^2 + c^2 + bc} = \frac{b^2 + c^2 + 2bc + b^2 + c^2}{b^2 + c^2 + bc} \]
\[ = \frac{2b^2 + 2c^2 + 2bc}{b^2 + c^2 + bc} \]
\[ = 2 \frac{b^2 + c^2 + bc}{b^2 + c^2 + bc} \]
\[ = 2 \]
Conclusion
The value of \(\frac{a^2}{a^2 – bc} + \frac{b^2}{b^2 – ca} + \frac{c^2}{c^2 – ab}\) is 2.
See less